ANALISIS TINGKAT KESEHATAN BANK UMUM TERHADAP HARGA SAHAM BANK MANDIRI TAHUN 2015-2019 - Kusumawardhani, Aninditha Putri; Saberina, Sabilla; Nursantika, Taufan (LPPM UNIBI, 2020)
This study aims to determine the effect of bank healthiness on stock prices especially in Bank Mandiri year 2015-2019. This research is to show that the Healthiness of a Commercial Bank is defined as the ability of a bank to carry out financial and banking operations normally and to be able to fulfill all its obligations in a manner that is in accordance with the prevailing laws and regulations. The regulations regarding the Healthiness of Commercial Banks that are applied in Indonesia cover various aspects of bank activities, from raising funds to the use and distribution of funds. Assessment of Commercial Bank Soundness includes an assessment of CAMEL (Capital, Assets Quality, Management, Earning, and Liquidity) factors. The objective of this research is healthiness of Bank Mandiri health enough because majority of indikator healthiness of Commercial Bank shows good result and maximal.